Managing the microbiological safety of blood for transfusion: a US perspective. (September 2009) - Dodd, Roger
For many decades, infectious disease was considered to be an unfortunate but unavoidable consequence of transfusion. However, since the early 1970s, the sequential introduction of numerous donor screening and testing methods along with continuous improvements has almost, but not completely, eliminated the risk of the classic transfusion-associated infections –– syphilis, hepatitis and retroviruses –– at least in the developed world. This has, at least in part, led to an increasing focus upon emerging infections: indeed, in the USA over the last few years, testing for West Nile virus (2003) and for antibodies to Trypanosoma cruzi (2007) have been implemented. This article will outline the current status of these and other transfusion-transmissible infections and discusses anticipated developments in the field. The perspective and the majority of the information is derived from experience in the USA.